Peningkatan Keterampilan Menulis Puisi melalui PjBL Berbantuan Media Canva pada Siswa MTs - Wahyuni, Eva; Eti Ramaniyar; Netti Yuniarti (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This research is motivated by the low poetry writing skills of grade VIII B students at MTs Mujahidin Pontianak, evidenced by a pre-cycle average score of 64% and a classical completeness rate of only 34%. The primary issues include students' difficulties in developing imagination, word choice (diction), and the limited use of innovative learning media. This study aims to improve poetry writing skills through the implementation of the Project Based Learning (PjBL) model assisted by Canva digital media. This study employed Classroom Action Research (CAR) conducted in two cycles, comprising planning, action, observation, and reflection phases. The research subjects consisted of 23 students. The results indicated a significant improvement in each cycle. The students' average score increased to 80% in cycle I and reached 87% in cycle II. Classical completeness also rose from 65% in cycle I to 86% in cycle II. The use of Canva was proven to stimulate students' creativity and motivation in expressing ideas into aesthetic poetry. The conclusion of this study is that the integration of the PjBL model and Canva media is effective in improving the quality of both the process and the learning outcomes of poetry writing. It is suggested that teachers adopt this model as an innovative alternative for literature learning in the digital era.